Rights‐Restricting Rhetoric: The Overseas Operations (Service Personnel and Veterans) Act 2021. Issue 2 (28th January 2022) - Mallory, Conall
Abstract: This article considers the role of rhetoric in British political discourse with a particular focus on how it aids the construction of legislation that restricts human rights. Using the parliamentary debates concerning the Overseas Operations (Service Personnel and Veterans) Act 2021 as an extensive example, it demonstrates how the rhetorical theatrics of legislating in the Westminster parliament play a fundamental role in justifying restrictions on rights to the public. Rhetoric fulfils three functions in this process: persuasion of the need for rights‐restricting legislation; obstruction of scrutiny of such plans, and the perpetuation of national myths and tropes upon which such policies are debated. Arguing that such rhetorical functions are immovable from British political discourse, the article concludes by proposing how they can best be diluted.